2019
DOI: 10.1080/24749508.2019.1600909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fireworks ancient celebrations on atmospheric concentration of particulate matter in Iran

Abstract: The Chahar-Shanbe Suri culture in Iran is a significant and direct factor leading to air pollution in Iran. This study investigates why and how "Chahar-Shanbe Suri" culture leads to increased air pollution in Iran. Following the fireworks of Chahar-Shanbe Suri in Tehran, Tehran's air quality index increased by a high slope, and the clean condition with the 49 index at 20 pm was unhealthy for all segments of society with a 177 index at 23 o'clock. Of course, according to the data measured in Tehran's air qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In Italy, Masiol et al (2014) reported high contribution for both PM10 (peak concentration of 700 µg/m 3 ) and trace gases during folk fires burnt on the eve of Epiphany (January), with average increase of between 65 and 200 µg/m 3 for PM10 and 90-235 µg/m 3 for PM2.5. Finally, in Iran, higher than average PM concentrations have been reported during the fireworks related to the Chahar-Shanbe Suri festival (Oroji et al, 2019). A summary of results in presented in Table 3.…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…In Italy, Masiol et al (2014) reported high contribution for both PM10 (peak concentration of 700 µg/m 3 ) and trace gases during folk fires burnt on the eve of Epiphany (January), with average increase of between 65 and 200 µg/m 3 for PM10 and 90-235 µg/m 3 for PM2.5. Finally, in Iran, higher than average PM concentrations have been reported during the fireworks related to the Chahar-Shanbe Suri festival (Oroji et al, 2019). A summary of results in presented in Table 3.…”
Section: Accepted Manuscriptmentioning
confidence: 87%